enetic Monsters: Loss of Innocence and Decision Making in Sleepaway Camp and XXY (Itinera, 2023)
Sleepaway Camp and XXY are two films that represent monstrosity from a genetic point of view. In this paper, I will analyze all the sexualities presented in both movies through the queer notion, and criticize the barriers imposed by heteronormative power to our un- derstanding of sexuality and the world, to fully understand the characters’ behaviors. This frame study will be also useful to acknowledge how repressions work, and of course how two movies with diverse style of filmmaking and from different contexts and times can assimilate those supposed monstrosities according to their own rules.
Keywords: sexual, genres, monstrosity, labels, queer